Improving Suppression of Hemipteran Vectors and Bacterial Pathogens of Citrus and Solanaceous Plants: Advances in Antisense Oligonucleotides (FANA) - Hunter, Wayne Brian; Cooper, William Rodney; Sandoval-Mojica, Andres F.; McCollum, Greg; Aishwarya, Veenu; Pelz-Stelinski, Kirsten S. (Frontiers in Agronomy, 2021)
We report on the development, evaluation, and efficient delivery of antisense oligonucleotide FANA (2′-deoxy-2′-fluoro-arabinonucleotide) RNA-targeting technology into citrus trees and potato plants for management of bacterial pathogens and arthropod pests. The FANA ASO technology is a single nucleotide strand of 20–24 nt in length that incorporates 2′F- chemically modifications of nucleotides, along with a phosphorothioate backbone and modified flanking nucleotides, in their structure called “gapmers,” produced by AUM LifeTech., Inc. These unique modified structures of FANA “triggers” enables gymnotic activity that self-delivers into cells, moving systemically in treated plants and insects, with significant suppression of their RNA targets. Reported is the FANA suppression of two plant-infecting bacterium Candidatus Liberibacter asiaticus, CLas (in citrus trees), and C. Liberibacter solanacearum, CLso (in potato and tomato). The CLas pathogen is associated with huanglongbing (a.k.a. Citrus Greening Disease), which causes severe loss of citrus trees, threatening global citrus production. The CLas bacterium is transmitted during feeding by the Asian citrus psyllid, Diaphorina citri (Hemiptera: Liviidae). CLso causes Zebra-Chip disease in potato and is transmitted by the potato psyllid, Bactericera cockerelli (Hemiptera: Triozidae). Infected citrus trees or potato plants were treated with aqueous FANA solutions applied as a soil drench, root-infusion, topical spray, tree trunk injection or by absorption into cuttings, detached leaves, and leaf disks. Plants showed significant reduction of each pathogen or symptom development in response to FANA treatments. Similarly, ingestion of FANA solutions designed specifically to CLas by insects via artificial diets produced significant titer reductions in infected citrus psyllid adults that resulted in reduction of CLas transmission. The unique properties of FANA ASO solves many of the problems of stability, cell entry, and binding affinity that plagues exogenous RNAi strategies. Breakthroughs in production methods are reducing costs enabling these ASO to expand beyond medical applications into agricultural treatments. Thus, FANA ASO may provide viable treatments in the response to crop pandemics, like huanglongbing in citrus that threatens global food production.